Leadership in the Digital Era: Inspiring and Strengthening Team Collaboration - alfizi alfizi; Aprista Eka Cahyani; Fera Septiani Rizqi; Rima Herawati Kurniawan; Zahroh Nur Hidayati Assakinah (Universitas Pekalongan, 2025)
This study explores the role of leadership in the digital era, with a focus on team collaboration and adaptation to rapid technological change. In the context of Enterprise/Society 5.0, leaders are expected to create a work environment that supports collaboration, where team members support each other and share knowledge to achieve common goals. Adaptive leadership is key, where leaders must understand technology and its impact on business. In the digital era, leaders need to have digital and emotional agility, as well as the ability to communicate effectively through digital platforms. Effective team collaboration is facilitated by digital tools that enable interactions across boundaries, time, and culture, thereby increasing operational efficiency. The research method used is a qualitative method with a literature study approach. This study emphasizes the importance of inspiring and motivating leadership to develop team potential in facing challenges in the ever-evolving digital era and also provides insight into how effective leadership can drive team collaboration and innovation in organizations amidst rapid technological change.